2020
DOI: 10.3390/sym12091438
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Symmetry in the Aesthetics of Residential Building Façades Using Cognitive Science Methods

Abstract: Symmetry is an important visual feature for humans and its application in architecture is completely evident. This paper aims to investigate the role of symmetry in the aesthetics judgment of residential building façades and study the pattern of eye movement based on the expertise of subjects in architecture. In order to implement this in the present paper, we have created images in two categories: symmetrical and asymmetrical façade images. The experiment design allows us to investigate the preference of subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…Symmetrical greenery may be perceived as unnatural, and according to our results, does not positively affect perceived restoration. The result may also be influenced by education and background, where artists and architects may have different preferences than nonexperts [40]. The aesthetic experience of building facades is influenced by people's expertise, with symmetrical facades corresponding to the taste of nonexperts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Symmetrical greenery may be perceived as unnatural, and according to our results, does not positively affect perceived restoration. The result may also be influenced by education and background, where artists and architects may have different preferences than nonexperts [40]. The aesthetic experience of building facades is influenced by people's expertise, with symmetrical facades corresponding to the taste of nonexperts.…”
Section: Discussionmentioning
confidence: 99%
“…The aesthetic experience of building facades is influenced by people's expertise, with symmetrical facades corresponding to the taste of nonexperts. Asymmetry may not necessarily lead to equal preferences for expert and nonexpert groups in eye movements in face images [40], and nonartistic individuals may find symmetrical and complex stimuli more beautiful [46]. Despite this, most studies have shown that visual qualities such as symmetry are influential in the visual preferences of architectural views.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the shape and appearance of a building, which might be symmetrical or asymmetrical, is the first thing that appears. People favor symmetry over asymmetry in this regard (Azemati et al, 2020). Individuals are more inclined to favor familiar buildings over unfamiliar buildings when they are exposed to them.…”
Section: Aesthetic Judgment and Aesthetic Distancementioning
confidence: 99%
“…What's more, studies showed that the differences in the cognition of viewers against things lead to the differences between the acceptance and impression levels [ 16 , 17 ]. Cook et al [ 18 ] studied the influence of personality on aesthetic preferences, and indicated that architectural familiarity was found to be highly predictive of preferences for all styles.…”
Section: Introductionmentioning
confidence: 99%